Ali je položaj javnega uslužbenca drugačen od položaja delavca skozi vidik delovnega razmerja - Korpič-Horvat, Etelka (Delavci in delodajalci, 2014)
The paper seeks an answer to the question whether the status of civil servants differs from that of other workers if the situation is assessed through the perspective of an employment relationship. Is it true that that public servants are more protected in the employment relationship and therefore in a better position than other workers; or has through greater equalisation of the public servant status with that of workers in the private sector regarding the labour relationship the situation of the civil servants significantly changed.
Keywords: delavci; delovno pravo; javna uprava; javni uslužbenci; pravno varstvo; zaposleni; zasebni sektor